Comparison of the Effectiveness of Hepatoprotectors of Black Cumin Extract and Temulawak Extract in SGOT and SGPT Induced by Paracetamol - Fadhilla Qudsi Ramadhani; Des Suryani (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2020)
ABSTRACT Background: Paracetamol is used for analgesics and antipyretics, its use can damage the liver. Herbs that prevent liver disorders are curcuma. Black cumin can increase antioxidants. Objective: This study aims to compare the effectiveness of black cumin extract and curcuma against the liver function of paracetamol-induced rats. Methods: A laboratory experimental study posttest only with control group design. A total of 4 groups were treated for 7 days. SGOT and SGPT levels were tested. Data analysis using one-way ANOVA post hoc Games-Howell.Results: K- and K+ groups in this study showed an increase in SGOT SGPT levels. There is an effect of giving a dose of paracetamol 500 mg/kgBB on liver damage, there is no differences and significant effect in the administration of black cumin extract and curcuma dose 500 mg/kgBB to the liver of rats that have been induced by paracetamol (p>0.05). Conclusion: Giving paracetamol has an influence on rat liver damage. And there was no difference in the effects of hepatoprotector in groups given black cumin extract and curcuma in paracetamol-induced rats. Keywords: black cumin, curcuma, paracetamol, SGOT, SGPT